Time and Design Construction for Costumes in the Iraqi Theater Show: محمــود جبــاري حــافظ (Al-Academy, 2020)
The theatre costume with the rest of the theatre show elements constitute a system of the meaning relations that produce a visual image that helps the recipient to decipher the theatre scene, let alone the manifestation of time in its levels (past, present, future) through the design construction of the theatre elements among which is the theatre costume. In order to know the way of manifesting time through the formulation of the theatre costumes, the research question has been put as follows: how to manifest time through the design construction for the theatre costumes unit, from which the research objective is derived as follows: Revealing the possibility of the designing unit of the costumes in manifesting the levels of time within the scenes of the theatre show. The research is divided into four chapters. The first (methodology) and the second (theoretical framework), and the third (procedures) in which a deliberate sample has been chosen, the play (picnic). The fourth chapter presents the research results and discussion as well as the conclusions and a list of sources.